On the research and the writing phase of the historian’s work - White, Hayden (Historein, 2013)
This comment on Chris Lorenz’s comment on my work indicates a number of typical failings of reviewers, of which Lorenz’s comments on my talk are typical. One, like most philosophers, Lorenz treats my work as a whole rather than as a congeries of individual works as if they were all written and published at the same time. He finds inconsistencies or contradictions between works written many years apart. My response is that many of these inconsistencies are a result of changes in my point of view over time. Secondly, instead of quoting a passage from my work and criticising it, Lorenz typically paraphrases an argument and then proceeds to criticise his own paraphrase. Often, I do not recognise the paraphrase as a position I hold. Third, I hold that historical writing is often and should be more associative than logical, more poetic than technical. Fourth, about causality in history, I do not think that we have any examples of a universal causal law of historical change or structure. So his demand for a causal law from me is beside the point.